Are children who are treated for asthma and seasonal allergic rhinitis disadvantaged in their educational attainment when acutely exposed to air pollution and pollen? A feasibility study. (2018) - Mizen, Amy; Lyons, Jane; Rodgers, Sarah; Berridge, Damon; Akbari, Ashley; Wilkinson, Paul; Milojevic, Ai; Doherty, Ruth; Dearden, Lorraine; Lake, Iain; Carruthers, David; Strickland, Sarah; et al.
No abstract available